Electrochemistry of porous materials - Doménech-Carbó, Antonio (Taylor & Francis, 2010)
Electrochemistry of Porous Materials focuses on generalized theoretical modeling and describes redox processes for different porous materials, assessing their electrochemical applications. Considering the large variety of materials that can be classified as porous, the text focuses on nanostructured micro- and mesoporous materials. Using this approach, the book offers a more focused and practical analysis of key porous materials that are considered relatively homogeneous from an electrochemical point of view. These include: Porous silicates and aluminosilicates; Porous metal oxides and related compounds; Porous polyoxometalates; Metal-organic frameworks; Porous carbons, nanotubes, and fullerenes; Porous polymers and certain hybrid materials.